Effects of subsidized health insurance on newborn health in Colombia (2008)
Colombia's rapid and considerable expansion of health insurance coverage in the1990s provides an opportunity to evaluate in a developing country whether health insurance increases the use of health care services and improves outcomes. Using regression discontinuity design we explore whether subsidized health insurance for the poor increases the use of health services and if it improves newborn health. Babies born from mothers with subsidized health insurance have a lower incidence of low birth weight. Extending the analysis to a period where there is evidence of manipulation in treatment assignment, we find that the positive effects disappear.